Neuropeptide Y mRNA expression in the aging inferior colliculus of fischer brown norway rats - Almassri, Laila S.; Crane, Kristen M.; Hergenrother, Sean R.; Singh, Gurveer; Barach, Gillian L.; Iafrate, Melina C.; Harris, Joshua C.; Tokar, Nick; Ohl, Andrew P.; Young, Jesse W.; Mellott, Jeffrey G. (Frontiers in Aging Neuroscience, 2025)
IntroductionA major contributor to age-related hearing loss is the decline of GABAergic inhibition, particularly in the inferior colliculus (IC), which is the midbrain hub of the central auditory system. The initial loss of inhibition is thought to be a compensatory mechanism in response to decreased peripheral excitation. However, the downregulation of inhibition in the IC persists with age and leads to functional disruptions and central neural gain. Neuropeptide Y (NPY) is co-expressed by a sub-population of GABAergic IC cells whose age-related changes remain unexplored. We sought to characterize GABAergic cells in the major subdivisions of the IC that express NPY mRNA to determine whether NPY mRNA is altered in aging IC cells.MethodsWe used multiplexed fluorescent in situ hybridization (smFISH) to label lemniscal and non-lemniscal IC cells that express NPY mRNA and/or GAD1 mRNA in four age groups of Fischer Brown Norway (FBN) rats.ResultsThe data demonstrate that ∼38% of GABAergic IC cells co-express NPY, the largest proportion of NPY cells is in the non-lemniscal dorsal IC (ICd), the majority of NPY cells have medium profile areas, and the expression of individual NPY mRNA is unaffected by age.DiscussionWhile GABAergic inhibition is reduced with age, it appears that NPY driven inhibition may remain intact. GABAergic neurons that co-express NPY may represent a marked population that persists throughout aging, suggesting that they are not the primary contributor to age-related loss of inhibition.